Pengaruh Model Index Card Match Terhadap Hasil Belajar Siswa Materi Fungsi Rangka Tubuh Manusia Kelas V SD Negeri 8 Koba - Amalia, Desti; Fitri Wardani, Erika; Kurnia, Feni (Universitas Muhammadiyah Bangka Belitung, 2024)
This research is hampered by a number of problems: teachers still practice book-centric learning and their pupils alone so that students are less enthusiastic at the time of learning. Then the functional matter of the human body frame has many components that complicate the student in understanding the matter. As a result, the student's learning results have not reached the KKM that is proven by the formative repetition results. The study aims to test the influence of the Index Card Match model on the learning results of students of the human body structure function material of class V in SD Negeri 8 Koba. This research is a quantitative approach with Pre-Experimental Design method with One Group Pretest-Posttest Design. The sampling technique used purposive sampling technique. The research subjects amounted to 28 students. Data collection techniques were carried out by giving tests in the form of essay questions. The data analysis technique uses normality test, homogeneity test and hypothesis testing using Paired Samples t Test.. The results of the study showed that the average value of the pre-test obtained 39.25 was categorized as less. The average of the posttest obtaining 82.12 was categorised as well. The result of the test of normality of the pretest 0.139 > 0.05 and the result of posttest normality 0.185 > 0.05. The test of the hypothesis with Paired Sampels T-test processed the value of 0.00 < 0.05. Based on the data description it can be concluded that there is an influence on the learning outcomes of students with the model Index Card Match material function of the human body frame class V SD Negeri 8 Koba.